Characterization of two types of polysaccharides from Eremurus hissaricus roots growing in Tajikistan. (August 2020) - Muhidinov, Zayniddin K.; Bobokalonov, Jamshed T.; Ismoilov, Ikromjon B.; Strahan, Gary D.; Chau, Hoa K.; Hotchkiss, Arland T.; Liu, LinShu
Abstract: Eremurus Hissaricus ( E.hissaricus ) is a native plant of Tajikistan that has been used in traditional medicine and whose raw components have been identified as having potential for the domestic economy. We have found that carbohydrates comprise 80–85% of the root biomass, from which we have characterized two types of polysaccharides: A water-soluble polysaccharide (WSP) and an acid-soluble polysaccharide (ASP), with 23% and 8% yields, respectively. The results from FTIR, HPAEC-PAD, HPSEC, methylation linkage analysis and NMR spectroscopy ( 1 H, 13 C, zTOCSY, HSQC, HSQCTOXY and HMBC) demonstrated that WSP has a backbone of (1 → 4)-linked β-d -mannopyranosyl and β-d -glucopyranosyl residues in a 1.5:1 M ratio, having acetylated groups, with weight-average molecular weights of 495 kDa. Analyses of ASP indicate that it is comprised of d -galactose, d -mannose, and d -glucose in a molar ratio of 1.8: 1.6: 1.0, which is consistent with a branched galactoglucomannan polysaccharide with (1 → 4)-linked β-pyranose configurations, and weight-average molecular weight of 179 kDa. The FTIR absorption bands in the region of 875–890 cm 1 and NMR spectroscopy data confirm the presence of β-pyranose configuration of main polysaccharide backbone in the both ASP and WSP samples. These polysaccharides are an available raw material with the potential for use in a number of industrial applications. Graphical abstract: Image 1 Highlights: Water- and acid-soluble polysaccharides were isolated from Eremurus Hissaricus roots. FTIR and NMR spectroscopy analysis show β-d -pyranose configuration of the WSP&ASP. The WSP contains glucomannan, while ASP is comprised of galactoglucomannan. The NMR spectra clearly established the presence of acetyl groups in both polysaccharides. The molecular weight of WSP and ASP determined by HPSEC was 495 kDa and 179 kDa.